2002
DOI: 10.1046/j.1471-4159.2002.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of Aβ42 production by NSAID R‐enantiomers

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) have been associated with reduced risk for Alzheimer's disease (AD) and selected NSAIDs racemates suppress b-amyloid (Ab) accumulation in vivo and Ab42 production in vitro. Clinical use of NSAIDs for preventing or treating AD has been hampered by dose-limiting toxicity believed to be due to cyclooxygenase (COX)-inhibition that is reportedly not essential for selective Ab42 reduction. Profens have racemates and R-enantiomers were supposed to be inactive forms. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
123
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 21 publications
10
123
2
Order By: Relevance
“…The results are also in line with previous clinical evidence showing that CHF5074 administration reduces TNFa levels in cerebrospinal fluid of healthy subjects and of MCI patients (Ross et al, 2013). Worth of note, the peculiar modulation of M2 microglial transcription by CHF5074 in primary cultures was not reproduced by the classical NSAID ibuprofen or by the atypical NSAID R-flurbiprofen devoid of cyclooxygenase inhibitory activity (Morihara et al, 2002). In line with previous evidence (Ogawa et al, 2000;Hinz et al, 2000;Heneka et al, 2005), either ibuprofen or R-flurbiprofen diminished iNOS mRNA, but neither compound modified MRC1 or TREM2 expression.…”
Section: Discussionsupporting
confidence: 83%
“…The results are also in line with previous clinical evidence showing that CHF5074 administration reduces TNFa levels in cerebrospinal fluid of healthy subjects and of MCI patients (Ross et al, 2013). Worth of note, the peculiar modulation of M2 microglial transcription by CHF5074 in primary cultures was not reproduced by the classical NSAID ibuprofen or by the atypical NSAID R-flurbiprofen devoid of cyclooxygenase inhibitory activity (Morihara et al, 2002). In line with previous evidence (Ogawa et al, 2000;Hinz et al, 2000;Heneka et al, 2005), either ibuprofen or R-flurbiprofen diminished iNOS mRNA, but neither compound modified MRC1 or TREM2 expression.…”
Section: Discussionsupporting
confidence: 83%
“…Considering the first of these three mechanisms, high dose ibuprofen (100-500 mM) has been shown to reduce Ab42 production in vitro, an effect also shown by other NSAIDs to be independent of their antiinflammatory effects on regulating COX, PPAR, and NFkB (Weggen et al, 2001;Morihara et al, 2002;Sagi et al, 2003;Takahashi et al, 2003). Although the COX-dependency of ibuprofen's effects on Ab42 suppression has not been tested, another NSAID sulindac has been more extensively analyzed and clearly reduces Ab42 independent of COX (Weggen et al, 2001;Sagi et al, 2003;Takahashi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The human ACT gene has enhancer elements responsive to IL-1-bstimulated NFkB and AP-1 (Kordula et al, 2000) and human ACT mRNA expression is directly controlled by NFkB (Lieb et al, 1996). As ibuprofen is a weak NFkB inhibitor (Tegeder et al, 2001), it is possible that higher levels of ibuprofen or the less toxic R-flurbiprofen (Morihara et al, 2002) could directly reduce human ACT expression levels by inhibiting NFkB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to these traditional views, however, it has recently been shown that a subset of NSAIDs (ibuprofen, sulindac sulfide (SSide), indomethacin, and R-flurbiprofen) selectively decrease the secretion of A␤42 from cultured cells independently of COX activity and lowers the amount of soluble A␤42 in the brains of transgenic mice (21,22). In cultured cells, the decrease in A␤42 secretion caused by SSide was accompanied by an increase in A␤38 generation, whereas the Notch site-3 cleavage activity to generate Notch intracellular domain (NICD) was not significantly affected.…”
mentioning
confidence: 99%